Selective proximal renal tubular involvement and dyslipidemia in two cousins with oculocerebrorenal syndrome of Lowe - Topaloğlu, Rezan; Ludwig, Michael; Çelebi Tayfur, Aslı (The Turkish Journal of Pediatrics, 2013)
Oculocerebrorenal syndrome of Lowe (OCRL) is a rare, X-linked disorder characterized by congenital cataracts, neonatal or infantile hypotonia, seizures, cognitive impairment, and renal tubular dysfunction. In this article, we report two maternal cousins with OCRL with a hemizygous p.Ala788Asp mutation in exon 22 of the OCRL gene. They presented with diverse features of selective proximal renal tubular defect and high serum levels of total cholesterol, low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C).